Language teacher education in Austria and Hungary (Training and Practice : Journal of Educational Sciences, 2019)
The success of language education is mainly dependent on the teacher and his/her professional preparedness, the basis of which starts at the education of the teacher him/herself. After the Bologna system reform, not only in Hungary but, also in Austria the teacher education, and within that the language teacher education had to be reformed. The two reforms on the other hand showed different directions, therefore the study will compare the structure of the Hungarian and the Austrian program, the duration of the program, the subjects of pedagogy, the scale of the practical part and the development of the language, the level of the students entering the program and the level of students leaving the program.